Effects of stocking density on performance, egg quality, reproductive hormones, and antioxidant capacity in egg-laying ducks. Issue 1 (1st January 2020) - Xiong, Xia; Yang, Yong; Jiang, Xiaosong; Yu, Chunlin; Peng, Han; Chen, Jialei; Xia, Bo; Du, Huarui; Li, Qingyun; Zhang, Zengrong; Yang, Li; Qiu, Mohan; et al.
ABSTRACT: This study was conducted to evaluate the effects of stocking density on productive performance, egg quality, and antioxidant capacity in laying ducks. A total of 720 20-week-old Jinding laying ducks were randomly assigned to 5 stocking densities (4, 5, 6, 7, and 8 birds/m 2 ) with 8 replicate pens each treatment. The results showed that increasing stocking density linearly increased egg production and egg mass and linearly decreased FCR of laying ducks ( P  < 0.05). The eggshell strength and thickness decreased linearly ( P  < 0.05) and quadratically ( P  < 0.05) with an increase in stocking density. Increased stocking density linearly decreased concentrations of estradiol-17β and follicle-stimulating hormone, activities of superoxide dismutase, glutathione peroxidase, and total antioxidant capacity in plasma ( P  < 0.05), but linearly increased plasma and hepatic malondialdehyde content ( P  < 0.05). The results suggested that high stocking density adversely influenced laying performance and egg quality of ducks, which is associated with impaired antioxidant capacity. Under our experimental conditions, we recommend that the stocking density of laying ducks should be kept to 4 or fewer birds/m 2 to avoid the negative effects of high stocking density on performance and egg quality of laying ducks.